Study on the eco-economic efficiency of China’s mariculture based on undesirable output - Jinli, Dong; Manhong, Shen; Xuan, Yu (Frontiers in Marine Science, 2023)
The marine ecological and environmental problems caused by the mariculture industry have drawn considerable attention. The Slacks-based measure (SBM) model was applied to measure the eco-economic efficiency of China’s mariculture industry from 2011 to 2020, where the nitrogen and phosphorus pollutants produced in the mariculture process were the non-desired outputs. The results indicated that the average value of mariculture eco-economic efficiency in different provinces of China was above 0.8 in the higher status. The σ and β convergence analysis verified that the differences in the eco-economic efficiency of mariculture in coastal provinces of China were shrinking significantly (P = 0.017 and 0.000, respectively). There are imbalances in regions as the change of the East China Sea and the South China Sea showed an approximately “U” shaped state. The Chinese government should continue to strengthen its economic and policy support for mariculture to ensure its long-term green and healthy development in a long time.